Experiential learning and the power of women - Falk, Thomas; Bartels, Lara Bartels; Steimanis, Ivo; Duche, V.; Vollan, Björn (International Food Policy Research Institute, 2023)
An emerging body of research explores the use of experiential learning games as an intervention to facilitate sustainable natural resource management. We conducted games with users of a local public good—a rainfed dam for irrigation—in 56 randomly selected villages in Madhya Pradesh, India. An additional 27 villages were randomly drawn as control sites. These communities depend on rainfed dams for complementary irrigation and our game reflected related key management challenges. Our study explores (1) the effect of playing the game on institutional and behavioral change; (2) how women’s participation (not exogenously determined) in economic learning games is related to the interventions’ outcomes and (3) what role women leaders play. We find a lasting direct treatment effect on actual dam maintenance while there is no effect on the existence of dammanagement rules. Using economic games as a learning intervention in 56 Indian communities showed that involving more women led to greater success in sustainable water management two years after the intervention. Although participation of female leaders did not directly influence management improvements, their presence did increase women’s participation in the games. Our study increased the confidence that games can play a critical role in designing natural resource management interventions. These findings underscore the significance of involving women in game-based learning for sustainable resource management.